2020
DOI: 10.3389/fonc.2020.01390
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes and Complications After Salvage Total Laryngectomy for Residual, Recurrent, and Second Primary Squamous Cell Carcinoma of the Larynx and Hypopharynx: A Multicenter Retrospective Cohort Study

Abstract: Background/Purpose: We analyzed complications and functional outcomes and aimed at identifying prognostic factors for functional outcomes and complications in patients who underwent salvage total laryngectomy (STL) for residual, recurrent, and second primary squamous cell carcinoma (SCC) of the larynx and hypopharynx after initial (chemo)radiation. Methods: Retrospective cohort study of patients who underwent STL in four major Belgian reference hospitals between 2002 and 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 48 publications
6
21
0
Order By: Relevance
“…Although, several studies already reported on functional endpoints after primary or salvage laryngectomy, laryngopharyngectomy, and on the usage of different flaps, we believe that our study has significant strengths providing new data that adds to the current literature [ 18 , 20 , 21 ]. First, we have shown long-term functional outcomes of patients with a mean follow-up time of 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, several studies already reported on functional endpoints after primary or salvage laryngectomy, laryngopharyngectomy, and on the usage of different flaps, we believe that our study has significant strengths providing new data that adds to the current literature [ 18 , 20 , 21 ]. First, we have shown long-term functional outcomes of patients with a mean follow-up time of 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation of speech is a major goal after laryngectomy [ 18 ]. Indeed, rates for voice rehabilitation range from approximately 80% in patients with laryngectomies to less than half in patients undergoing pharyngectomy with a need for free flap reconstruction [ 14 , 19 , 20 ]. In our cohort, voice rehabilitation was achieved in more than two-thirds with valved voice prosthesis insertion and sufficiently acquired esophageal speech.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, salvage treatments may also allow to a fairly good outcome. Nevertheless, both surgery and re-irradiation are burdened by not insignificant toxicities, and importantly, by a high rate of second and third recurrences [ 77 , 78 ]. Therefore, research on the possible means of enhancing the anti-PD-1 effect, and overall, the systemic therapy effect, is much needed.…”
Section: Discussionmentioning
confidence: 99%
“…The rehabilitation rate is influenced by the type of intervention utilized. Some studies show percentages for patient voice recovery in the range of 80% for patients who have undergone laryngectomies and under 50% for pharyngectomy, which requires a free flap rebuilding [93]. Multiple studies are focusing on the endpoints for laryngectomy or laryngopharyngectomy, approaching variations of flap types [94].…”
Section: Voice Prosthetics Rehabilitationmentioning
confidence: 99%